(untitled) (International Journal of Environmental Sciences, 2025)
This research examines the wound healing efficacy of an ethanol extract derived from Pergularia daemia leaves, employing a full-thickness excision wound model in mice. The study contrasts the outcomes of the plant-based formulation with povidone-iodine (standard treatment) and paraffin (control). Animals were divided into three groups and treated topically for 14 consecutive days. Key healing parameters such as wound contraction rate, duration of epithelialization, microbial load reduction, and histopathological tissue response were assessed over a 14-day period. The findings indicate that the P. daemia extract demonstrates noteworthy wound healing and antimicrobial activity,nearly equivalent to the standard drug, underscoring its potential utility as a natural alternative in topical wound care therapies. These outcomes favor the medicinal value of P. daemia in topical wound care and encourage its integration into phytotherapeutic formulations as a cost-effective and natural alternative. Furthermore, its wide availability, historical ethnomedicinal usage, and biocompatibility make it a potential candidate for community-level therapeutic interventions where access to conventional medicine is limited. Additional studies focusing on molecular mechanisms and isolation of bioactive constituents will enhance our understanding of its mode of action and assist in developing novel botanical formulations.